Аналітико-числове розв'язування задачі розсіяння електромагнітних хвиль малими включеннями - Андрійчук, М.І. (Фізико-механічний інститут ім. Г.В. Карпенка НАН України, 2010)
Combination of the asymptotical approach and numerical solution of respective integral Fredholm equations of the second kind is applied for solving the electromagnetic field scattering problem by the set of small particles. Impedance boundary conditions are assumed on the boundaries of small particle. The results of numerical simulation show good agreement with the theory. They open a way to numerical implementation of the method for creating media with a desired refraction coefficient.